Gender Differences in Head Teachers’ Work Motivation for Assuming Diverse Job Roles - Nikičić, Igor; Varga, Rahaela (Revija za elementarno izobraževanje, 2025)
This paper explores the characteristics of gender differences in work motivation for assuming the diverse job roles of head teachers in their everyday work in Croatia. Grounded in the well-established self-determination theory (SDT), this paper examines not only the intensity of motivation among head teachers, but also its quality, while applying the WRMS – SP questionnaire. The findings have important implications in recognizing the gender-based similarities in motivation types as confirmation that both men and women perceive themselves as effective leaders in a complex job role and present-day challenges in schools.